Pressure Vessel Mechanical Design Case study for 10 kg/cm² Pressure and 179 C Temperature - Sumanto Sumanto; Yuni Pita Asmiran; Pedro Da Silva; Hendra Gunawan; Acim Maulana (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2021)
Pressure vessel is a closed tube that holds pressure, both internal pressure and external pressure. This pressure vessel is designed to function as a reservoir for condensate or condensed water and convert it into steam or hot steam. This article discusses the design of a pressure vessel for a pressure of about 10 kg/cm² and a design temperature of 179oC. In the design of this pressure vessel, it includes determining the material to be used in the design, determining the allowable stress of each material used, determining the cylinder wall thickness, cylinder head or cover wall thickness, nozzle wall thickness, determining the maximum allowable working pressure limit. or maximum allowable working pressure and testing after the pressure vessel is finished, namely the hydrostatic test method. The design has been successfully carried out according to the provisions. Bejana tekan atau pressure vessel adalah suatu tabung tertutup penampung tekanan, baik tekanan dari dalam maupun tekanan dari luar bejana. Bejana tekan yang ini dirancang berfungsi sebagai penampung condensate atau air kondensasi dan mengubahnya menjadi steam atau uap panas. Pada artikel ini dibahas perancangan pressure vessel untuk tekanan sekitar 10 kg/cm² dan suhu rancang 179oC. Dalam perancangan bejana tekan ini meliputi pemilihan material yang akan digunakan dalam perancangan, menentukan tegangan yang diijinkan atau allowable stress dari setiap material yang digunakan, menentuan tebal dinding silinder, tebal dinding head atau penutup silinder, tebal dinding nozzle, menentuan batas tekanan kerja maksimum yang diijinkan atau maximum allowable working pressure dan pengujian setelah bejana tekan jadi yaitu dengan metode hydrostatic test. Dalam artikel ini perancangan secara numeris telah berhasil dilakukan dengan baik sesuai ketentuan.